2012
DOI: 10.1111/j.1365-2249.2011.04529.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage cell pattern from healthy human lung

Abstract: SummaryBronchoalveolar lavage (BAL) is widely accepted as a key diagnostic procedure in interstitial lung diseases (ILD). We performed a study to obtain reference intervals of differential cell patterns in BAL fluid with special attention to the origin of lavage fluid, e.g. bronchial/alveolar, to atopy and smoking status and to age of the healthy people. We performed bronchoalveolar lavage in 55 healthy subjects with known atopy status (age: 18-64 years, nonsmokers/smokers: 34/21) and determined differential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 35 publications
6
68
1
3
Order By: Relevance
“…Alveolar macrophages are the most common cell type within airways and are the front line of defense in pulmonary bacterial infections (25). These innate immune cells have multiple mechanisms by which they clear bacteria from airways: phagocytosis, respiratory burst (26), AMP production (27), and extracellular trap formation (28).…”
Section: Resultsmentioning
confidence: 99%
“…Alveolar macrophages are the most common cell type within airways and are the front line of defense in pulmonary bacterial infections (25). These innate immune cells have multiple mechanisms by which they clear bacteria from airways: phagocytosis, respiratory burst (26), AMP production (27), and extracellular trap formation (28).…”
Section: Resultsmentioning
confidence: 99%
“…Pure populations of neutrophils are not usually encountered in vivo ; instead neutrophils are usually encountered as part of a heterogenous mixture of leukocytes and epithelial cells (Farrera and Fadeel, 2013; Heron et al, 2012; Nicu and Loos, 2016; Werner et al, 2011). Since these other cell types also express Fc receptors, pathogen recognition receptors, and/or selectins (Golebski et al, 2015; van Tongeren et al, 2015), we sought to determine whether the relationship described in Equation 1 could accurately measure neutrophil content in a heterogenous sample containing nasal epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, burn injuries are also rich in neutrophils and epithelial cells, making burned skin samples a good candidate for examination by this method. However, other leukocytes highly express CD16, CD18, and CD62L, and are abundant in the lungs during inflammation (Ghoneim et al, 2013; Heron et al, 2012), so this method is unlikely to be accurate with BALF. A recent study of BALF in various human diseases found that neutrophils typically made up only 6% of BALF cell content, while alveolar macrophages and lymphocytes constituted 86% (Wojtan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority (>85%-96%) of cells obtained from healthy human volunteers by BAL are AMs [3,5,35,36]. Most of the lysates from sham-exposed AMs and AMs exposed to virus in the presence of antiyellow fever virus antibody (lanes 2 and 3, respectively), and lysate from AMs exposed to IAV in the presence of nonneutralizing anti-IAV antibody (lane 4).…”
Section: Discussionmentioning
confidence: 99%